Among the Eunuchs: A Muslim Transgender Journey - Jagiella, Leyla (Hurst Publishers, 2021)
Intro -- Half Title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- Glossary -- Preface -- Introduction: Life in the House -- 1. A Transnational Journey -- 2. The Unbearable Whiteness of Being -- 3. Eunuchs, Shemales, Transsexuals -- 4. The Genders of Islam -- 5. On the Path of the Saints -- 6. Being a Woman -- 7. Let's Talk About Sex -- 8. Crime and Prejudice -- 9. Islamism and Islamophobia -- 10. Sex and the Cosmopolis -- Conclusion: Past, Present and Future -- Notes -- Back Cover.